Pirfenidone in chronic hypersensitivity pneumonitis: a real-life experience - Shibata, Sho; Furusawa, Haruhiko; Inase, Naohiko (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Pirfenidone is an antifibrotic drug used for the treatment of idiopathic pulmonary fibrosis. Objectives: The aim of this study was to evaluate the efficacy of pirfenidone in patients with chronic hypersensitivity pneumonitis (HP). Methods: Twenty-three patients with chronic HP treated with pirfenidone were enrolled in this study based on a retrospective medical record review. Results: The change in vital capacity (VC) in the 6 months after the start of treatment (-152±56.1 ml) was significantly improved compared with that in the 6 months before treatment (-292±77.8 ml, p=0.047). No patients discontinued the treatment with adverse events. Conclusions: These results demonstrate that pirfenidone may reduce the decline of VC in patients with chronic HP without eliciting significant adverse events.